(untitled) (Research, Society and Development, 2020)
Objective: to carry out a bibliographic survey on or use of medicinal plants that are not treated for obesity. Methodology: the research is about an integrative review of the literature in which foram carried out you are looking for by authors following databases PubMed, ScienceDirect, BVS, published between the years of 2015 to 2020. In total, 255 studies were found, of which 13 were selected for the review synthesis. Results and Discussions: verified a variety of plants popularly used for the treatment of obesity, being that 14 species of plants have potential activity against the subject under study, which highlights the following plants: Camellia sinensis, Ilex paraguariensis, Garcinia cambogia and 2 plants requiring more in vitro and in vivo studies at B. trimera and A. muricata. Of all the selected studies, only 1 study or toxicity profile of the studied plant (M. oleifera). Conclusion: it is emphasized the need to carry out studies that address biological activities, but also demonstrate the toxicity of the studied product so that it has a safety band that allows a possible choice or disposal of investment by the pharmaceutical industry.